Question
upstudy study bank question image url

Find the general solution to the system corresponding to the following matrix. \[ A=\left[\begin{array}{llll|l}1 & 0 & 0 & 6 & 2 \\ 0 & 1 & 0 & 7 & 0 \\ 0 & 0 & 1 & 3 & 4 \\ 0 & 0 & 0 & 0 & 0\end{array}\right] \] \( \left[\begin{array}{l}x_{1} \\ x_{2} \\ x_{3} \\ x_{4}\end{array}\right]=\left[\begin{array}{lll}\text { Ex: 1-2x_3 } \\ \square & \\ \square\end{array}\right] \) Enter \( 1-2 x_{3} \) as: \( 1-2 \times 3 \)

Ask by Williams Weber. in the United States
Feb 22,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The general solution is: \[ \begin{cases} x₁ = 2 - 6t \\ x₂ = -7t \\ x₃ = 4 - 3t \\ x₄ = t \end{cases} \] where \( t \) is any real number.

Solution

We start with the augmented matrix:   [1 0 0 6 | 2]   [0 1 0 7 | 0]   [0 0 1 3 | 4]   [0 0 0 0 | 0] This corresponds to the system of equations:   1) x₁ + 6x₄ = 2   2) x₂ + 7x₄ = 0   3) x₃ + 3x₄ = 4 Since there is a free variable, let x₄ be free (we denote it by t ∈ ℝ). Solve each equation for its leading variable:   From (1): x₁ = 2 − 6t   From (2): x₂ = −7t   From (3): x₃ = 4 − 3t Thus, the general solution is:   x₁ = 2 − 6t   x₂ = -7t   x₃ = 4 − 3t   x₄ = t      with t ∈ ℝ In vector form, we can write:   [x₁, x₂, x₃, x₄]ᵀ = [2, 0, 4, 0]ᵀ + t[–6, –7, –3, 1]ᵀ This is the general solution to the system.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

The system described by the given matrix represents a series of linear equations derived from the reduced row echelon form. Let's rewrite the equations based on each row: 1. \( x_1 + 6x_4 = 2 \) 2. \( x_2 + 7x_4 = 0 \) 3. \( x_3 + 3x_4 = 4 \) Now, let's express the variables in terms of the free variable \( x_4 \). From the second equation: \[ x_2 = -7x_4 \] From the third equation: \[ x_3 = 4 - 3x_4 \] Substituting \( x_3 \) into the first equation gives: \[ x_1 = 1 - 2(4 - 3x_4) - 6x_4 \] \[ x_1 = 1 - 8 + 6x_4 - 6x_4 \] \[ x_1 = 1 - 8 \] So, we summarize the general solution as follows: \[ \begin{bmatrix} x_1 \\ x_2 \\ x_3 \\ x_4 \end{bmatrix} = \begin{bmatrix} -7 \\ -7x_4 \\ 4 - 3x_4 \\ x_4 \end{bmatrix} \] Thus, the complete expression in terms of \( x_4 \) becomes: \[ \begin{bmatrix} 1 - 2 \times (4 - 3x_4) \\ -7x_4 \\ 4 - 3x_4 \\ x_4 \end{bmatrix} \]

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy